Optineurin: A Coordinator of Membrane-Associated Cargo Trafficking and Autophagy - Ryan, Thomas A.; Tumbarello, David A. (Frontiers in Immunology, 2018)
Optineurin is a multifunctional adaptor protein intimately involved in various vesicular trafficking pathways. Through interactions with an array of proteins, such as myosin VI, huntingtin, Rab8, and Tank-binding kinase 1, as well as via its oligomerisation, optineurin has the ability to act as an adaptor, scaffold, or signal regulator to coordinate many cellular processes associated with the trafficking of membrane delivered cargo. Due to its diverse interactions and its distinct functions, optineurin is an essential component in a number of homeostatic pathways, such as protein trafficking and organelle maintenance. Through the binding of polyubiquitinated cargoes via its ubiquitin binding domain, optineurin also serves as a selective autophagic receptor for the removal of a wide range of substrates. Alternatively, it can act in an ubiquitin-independent manner to mediate the clearance of protein aggregates. Regarding its disease associations, mutations in the optineurin gene are associated with glaucoma and have more recently been found to correlate with Paget’s disease of bone (PDB) and amyotrophic lateral sclerosis (ALS). Indeed, ALS-associated mutations in optineurin result in defects in neuronal vesicular localisation, autophagosome-lysosome fusion and secretory pathway function. More recent molecular and functional analysis has shown that it also plays a role in mitophagy, thus linking it to a number of other neurodegenerative conditions, such as Parkinson’s. Here we review the role of optineurin in intracellular membrane trafficking, with a focus on autophagy, and describe how upstream signalling cascades are critical to its regulation. Current data and contradicting reports would suggest that optineurin is an important and selective autophagy receptor under specific conditions, whereby interplay, synergy and functional redundancy with other receptors occurs. We will also discuss how dysfunction in optineurin-mediated pathways may lead to perturbation of critical cellular processes, which can drive the pathologies of number of diseases. Therefore, further understanding of optineurin function, its target specificity, and its mechanism of action will be critical in fully delineating its role in human disease.